Nursing care for women with postpartum depression in primary health care (Research, Society and Development, 2022)
Postpartum depression is the most common and disabling psychiatric condition during the puerperium and it is through primary health care that nurses work to identify symptoms, providing comprehensive and humanized care. The objective of this study was to identify, through an integrative literature review, how nursing care is given to women with postpartum depression in primary health care. This is an integrative literature review in the following databases: BDENF, SciELO, MEDLINE and Web of Science, using the descriptors: Primary Health Care; Postpartum Depression and Nursing Care. Inclusion criteria were: complete articles, dissertations or theses, published in the last five years (2016 to 2021, in Portuguese, English or Spanish. Monographs, letters to the editor, integrative reviews and research that were not available in full electronically were excluded A total of 11 articles were identified, grouped into two thematic categories: nursing care strategies for women with postpartum depression and challenges of nursing care for women with postpartum depression in primary health care. of nursing care through nursing consultation actions, home visits, matrix support, among others. There was a lack of knowledge of nurses, predominance of the biomedical model and fragmented care, resulting in difficulty in early diagnosis, signaling the need for permanent education of nurses, aiming to provide comprehensive and quality care.